Role of Udumbara (Ficusracemosa Linn) In The Management of Vidradhi – A Drug Review: Pharmaceutical Science-Pharmacology - Nycy, Dr. B. S.; Rajkumar Gupta, Dr.; Bharat Rathi, Dr.; Pramod Khobragade, Dr. (International Journal of Life Science and Pharma Research, 2023)
Acharya Susruta has extensively discussed the concept of vidradhi. He used the word “Sheegra vidahivat" to indicate its immediate burning nature. Prevalence of perianal abscess common in clinical practice. The Materia Medica of Ayurveda gives large information on therapeutically critical herbal products. An abscess is a localized collection of pus and a limited assortment of discharges in a depression shaped from tissues that irresistible bacteria have separated. An abscess is caused when microscopic organisms such as staphylococci or streptococci admittance to strong tissue like a wound on the skin. In traditional drug practices, distinct parts (leaves, stem, root, fruit, seeds, latex or even entire plant) of Ficus Racemosa Linn. are used to manage abscess. Its Sanskrit name is Udumbara, commonly known as gular in Hindi. Ficus Racemosa Linn. has confirmed various pharmacological actions like hypoglycemic, hypolipidemic, anti-carcinogenic, antidiuretic, hepatoprotective, anti-ulcer, and antifungal. β-sitosterol and glauanol acetate are the phytoconstituent found in Ficus Racemosa Linn. In the present review management of vidradhi with Udumbara (Ficusracemosa Linn) as ekal dravya (mono drug) with the expected mode of action has been explained. Most of the reviews of the Udumbara (Ficus Racemosa Linn) drug have not explained its effect on managing vidradhi (abscess) with its mode of action. Understanding the mode of action of Udumbara at different stages of shadkriyakala of vidradhi will help better administer the herb and prevent complications. Various Ayurvedic classical texts, Research portals like PUBMED, Google scholar, SCOPUS, DHARA and AYUSH Namaste portal are searched for the data collection: Udumbara (Ficusracemosa Linn) being Kashaya, Madhura rasa, Sheeta veerya, Katu vipaka and ruksha guna acts as pitta kapha shamaka and is a drug of choice in this condition.